96.4k views
2 votes
Factor:X^3-5x^2+7x-12: (x-4)(x^2-x+3) show all work

User Trant
by
6.3k points

1 Answer

2 votes

Explanation:

Given a polynomial of X^3-5x^2+7x-12, we can factor this by first identifying the trailing coefficient of the constant tern which is -12, and then find its factors with plus, or minus.

12 = 12 × 1 = 6 × 2 = 4 × 3 = 2 × 2 × 3 = 3 × 2 × 2.

4 is the factor we are looking for so we can use synthetic division to find the missing factor because we know (x-4) is one of them.

so (x^3-5x^2+7x-12)/(x-4) = (x^3-5x^2+7x-12) ÷ (x-4)

User Linn
by
6.1k points